EFFECT OF INVENTORY OPTIMIZATION ON PERFORMANCE OF STATE CORPORATIONS IN KENYA - Kazungu, Robert Riziki; Ochiri, Dr. George (International Journal of Supply Chain and Logistics, 2019)
Purpose: the general objective of was to determine role of inventory optimization on performance of state corporations in Kenya. Methodology: This research study adopted a descriptive research design approach targeting heads of procurement at the 187 state corporations. This method was preferred because it allowed an in-depth study of the subject. The study preferred this method because it allowed an in-depth study of the subject. To gather data, structured questionnaire will be used to collect data from 187 respondents. The research focused on primary data that was collected from questionnaires distributed to the target groups. This study collected both qualitative and quantitative data. After data collection the data was edited and coded in readiness for analysis by the researcher. The qualitative data collected was subjected to content analysis. On the other hand, the study used descriptive and inferential statistics to analyze the quantitative data. This study utilized the SPSS version 23 software to perform correlation and regression analysis on the collected data. The analyzed data was presented using statistical and graphical techniques Results: R square value of 0.768 means that 76.8% of the corresponding variation in performance of state corporations in Kenya can be explained or predicted by (safety stock management, inventory control techniques, information technology integration and demand and supply forecasting) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (Î² = 0.761), p=0.000 <0.05). Conclusion: The findings of the study indicated that; safety stock management, inventory control techniques, information technology integration and demand and supply forecasting have a positive relationship with performance of state corporations Policy recommendation: the study recommended that public institutions should embrace inventory optimization practices so as to improve their performance.